2015
DOI: 10.1002/2014jb011384
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and interpretation of subtle deformation signals at Unimak Island from 2003 to 2010 using weather model‐assisted time series InSAR

Abstract: A 7 year time series of satellite radar images over Unimak Island, Alaska-site of Westdahl Volcano, Fisher Caldera, and Shishaldin Volcano-was processed using a model-free Persistent Scatterer Interferometry technique assisted by numerical weather prediction model. The deformation-only signals were optimally extracted from atmosphere-contaminated phase records. The reconstructed deformation time series maps are compared with campaign and continuous Global Positioning System (GPS) measurements as well as Small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…We subsequently model and subtract stratified atmospheric phase signals (φ i,j,atm−s ) from Equation (2) using the Weather Research and Forecasting (WRF) model and following the approach described in Gong et al, [46,47]. This separate step is required as stratified atmospheric signals are significant at Augustine and can often not be removed using spatial or temporal filters.…”
Section: Methods: Differential Insar (D-insar) Time-series Processingmentioning
confidence: 99%
“…We subsequently model and subtract stratified atmospheric phase signals (φ i,j,atm−s ) from Equation (2) using the Weather Research and Forecasting (WRF) model and following the approach described in Gong et al, [46,47]. This separate step is required as stratified atmospheric signals are significant at Augustine and can often not be removed using spatial or temporal filters.…”
Section: Methods: Differential Insar (D-insar) Time-series Processingmentioning
confidence: 99%
“…[]. The horizontal velocity field found near Alaska's Pacific coast and to the west of longitude 155°W is complex due to volcanic and seismic activities [ Cross and Freymueller , ; Gong et al ., ]. The horizontal velocity field occurring in northeastern Alaska remains uncertain due to a lack of geodetic data and to ongoing postseismic motion associated with the M 7.9 Denali Fault earthquake of 2002.…”
Section: Horizontal Velocity Fieldmentioning
confidence: 99%
“…Previous studies have shown that a spherical “Mogi” source is sufficient to model the volcanic deformation at Westdahl and Makushin volcanoes (Gong et al, 2015; Lu et al, 2002, 2003; Mann & Freymueller, 2003). Akutan has a more complex magma plumbing system (DeGrandpre et al, 2017), but we found a Mogi source is still sufficient enough for studying the volume change history of Akutan volcano because the largest inflation events were well described by a Mogi source (Text S4).…”
Section: Methodsmentioning
confidence: 99%
“…Lu et al (2003) and Gong et al (2015) processed the InSAR images/time series using ERS1/2 and ENVISAT data for Westdahl volcano throughout the period of the 1990s and 2000s. For Makushin volcano, Lu et al (2002) and Lu and Dzurisin (2014) processed the InSAR images using ERS1/2 and ENVISAT data.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation